Asian summer monsoon influence on chemical weathering and sediment provenance determined by clay mineral analysis from the Indus Submarine Canyon. Issue 1 (January 2020) - Li, Yuting; Clift, Peter D.; Murray, Richard W.; Exnicios, Elise; Ireland, Thomas; Böning, Philipp
Abstract: Clay minerals from the Indus Canyon and eastern clinoform since 12 ka are uniformly rich in smectite and illite, similar to those from the Holocene Indus flood plains. A systematic enrichment of smectite in the proximal delta compared to the canyon and eastern clinoform argues for preferential capture of smectite close to the river mouth since 12 ka. There is a rapid shift to a more smectite-rich assemblage in the canyon and eastern clinoform after 5 ka. This change is probably caused by a change in sediment source, with less direct flux from the Himalaya and more erosion of older, weathered, smectite-rich sediment from the Indus River flood plains, driven by incision of the Indus and its tributaries into the floodplain as summer monsoon rains weakened. This influx of smectite is consistent with lower kaolinite/smectite values since 5 ka. The onset of large-scale agricultural activities since 5 ka, especially starting with the Harappan Civilization, may also have enhanced incision and erosion of floodplain sediments over the same time period. This study reports for the first time how monsoon strength variations since 12 ka affected the clay mineral assemblages and sediment provenance in a major submarine canyon.